HYDROLOGICAL STUDIES OF MATATILLA RESERVOffi, UTTAR PRADESH - JAIN, K. K.; SHERRY, P. M. (Journal of Indian Fisheries Association, 2015)
Matatilla reservoir, located in semi" arid region, (Lat 25Â° 15' N and Long. 78Â° 23'E) hasan area (at FRL) of 13,893 ha, volume and shore development 0.663 and 1.65, shoreline 73.6km. Volume and shore development indicate that greater pmi of the reservoir is shallow,which is a favourable point for fish productivity. Temperature and dissolved oxygen graduallydecreased with the increase in depth. Carbon dioxide was absent from the surface butinvaRiably present in the bottom (3.6 ppm). pH remained alkaline (7.2-8.4 ppm) throughoutthe year. Alkalinity, chlmide, calcium, magnesium, hardness and productivity was maximumin premonsoon and minimum in monsoon except for calcium and magnesium in postmonsoon.Phosphate, nitrogen and ammonical nitrogen were found in traces. These variations may bedue to influx and outflow of water and use of reservoir water for multipurpose activities.